Penerapan Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) Dalam Mewujudkan Good Governance Pada Politeknik Negeri Padang - Andriani, Wiwik; Rosita, Irda; Ihsan, Hidayatul (Jurusan Akuntansi Politeknik Negeri Padang, 2015)
Government Performance Accountability Report (LAKIP) as a part of Government Performance Accountability System (SAKIP) has an important role in good governance implementation in every government agency. This study aims to observe the implementation of SAKIP in oreder to achieve good governance in Padang State of Polytechnic (PNP). Based on LAKIP review by Directorate General of Higher Education in 2011, PNP got â€œAdequateâ€ result. The LAKIP review result increased in 2012 and 2013. Data was collected through questionnaires based on government agency performance accountability woking paper relesed in Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform Number 13/2010. Items to be evaluated are (1) performance planning (Strategic Plan/Renstra), Annual Performace Plan/Renja, and Performance Establisment), (2) performance meaurement, (3) performance repoting, (4) performance evaluation, and (5) performance achievement.